Directional Drilling Design Using Computer Model (University of Khartoum Engineering Journal, 2022)
The number of directionally drilled wells in Sudan is progressively increasing. Directional drilling calculations when done manually or through Microsoft Excel are tedious, susceptible to mistakes and take long time. The software prescribed in this paper is designed to treat these problems. This paper describes Software called CDD which stands for Computerized Directional Drilling. It is employing the minimum curvature method using visual basic (VB.NET) as a programming language to achieve calculations and minimize the uncertainty and risks related to achieve a predetermined target. The Software is capable of calculating the survey data of the well trajectory for all types of directional drilling wells. In addition, the CDD computes the actual coordinates along the planned trajectory at regular or irregular intervals and designs plots to show the well trajectory in 2D charts in top and side views. It also gives 3D graph for more visual representation of the well trajectory. The CDD enables the user to compare different well trajectories and show them in the same chart. The input data could be saved in the database section and the output results could be exported into various formats. Based on applying the CDD on the Case Studies, this Software gives accurate results and can be used in planning of CDD with error of less than 1%.